JARINGAN KOMUNIKASI PADA BIRO ORGANISASI DAN REFORMASI BIROKRASI SEKRETARIAT DAERAH PROVINSI DKI JAKARTA - Namira Tasya Syauki, (2021)
Not only Bureaucracy and Hierarchy, Communication Network is one of the things that can support the success of an organization. The interaction of the members of the organization is being studied so that a communication network is formed as the implementation of Bureaucratic Reform in government agencies. Bureau of Organization and Reform Bureaucratic of the Regional Secretariat of DKI Jakarta Province as the object of the communication network research. The objectives of this research are; Mapping the connection between actors in the network, Explaining sub-groups or cliques and the specific roles of actors in the network, and Explaining the structure of communication networks in the form of the degree of system connectedness, the average system connectivity and density in the communication network system The approach in this research is quantitative using a questionnaire Name Generator, Name Interpreter and Name Interrelaters which are distributed to all employees of the Bureau ORB of the DKI Jakarta Provincial Secretariat as many as 45 people. The results of this study describe the overall communication network in the Bureau ORB with a low density value of 0.082 and an ASC of 162 or 16% of possible relationships and 11.38% of centralization, which means that the percentage tends to lead to decentralization or a circular pattern. Keywords: Communication Network, Actors, Bureau ORB DKI Jakarta